Peran Penggunaan Media Sosial Terhadap Kinerja UMKM : Suatu Kajian Literatur Sistematik - M.Syamsul Hidayat; Kasnowo Kasnowo; Eny Setyariningsih (Journal of Economic, Bussines and Accounting (COSTING), 2022)
In the current business development that is growing, it is necessary for companies (UMKIM) to always carry out strategies in order to win the competition and ultimately improve their business performance. Social Media. There are many discussions with different results regarding social media and its impact on MSME performance. Therefore, this article aims to provide a clearer understanding of the influence of social media on MSME performance by conducting a systematic literature review of 10 publications published relevant from 2018 to 2022. The results of the analysis identify that in general social media has an influence on MSME performance in various countries. Keywords: Social Media, MSMEs, Systematic literature review.